2021
DOI: 10.1039/d1tc00283j
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the gate dielectric properties of vinyl-addition polynorbornene copolymersviathiol–ene click chemistry for organic field-effect transistors

Abstract: The control of gate dielectric properties of vinyl-addition polynorbornene copolymers bearing pendant vinyl groups for OFET applications is demonstrated through photoinitiated thiol–ene click chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The overall results are compiled in Table . There have been some reports about the vinyl-addition polymerization of n -alkyl-substituted NBs using diverse palladium catalyst systems, but the preparation of NB/ n -alkyl-substituted NBs copolymers with various monomer contents using these catalytic system has not been considered. , In our previous study, the Pd 2 (dba) 3 /PCy 3 /Li­[FABA] system had shown efficient copolymerization of NB with 5-vinyl-2-norborene, which produced the copolymers with the high molecular weights in high yields and showed a similar composition of the copolymer to the monomer feed ratio . Thus, we applied this three-component catalyst system to the copolymerization of NB and NBC x with varying monomer contents.…”
Section: Resultsmentioning
confidence: 99%
“…The overall results are compiled in Table . There have been some reports about the vinyl-addition polymerization of n -alkyl-substituted NBs using diverse palladium catalyst systems, but the preparation of NB/ n -alkyl-substituted NBs copolymers with various monomer contents using these catalytic system has not been considered. , In our previous study, the Pd 2 (dba) 3 /PCy 3 /Li­[FABA] system had shown efficient copolymerization of NB with 5-vinyl-2-norborene, which produced the copolymers with the high molecular weights in high yields and showed a similar composition of the copolymer to the monomer feed ratio . Thus, we applied this three-component catalyst system to the copolymerization of NB and NBC x with varying monomer contents.…”
Section: Resultsmentioning
confidence: 99%
“…Other VA-PNBs that could be easily subjected to further functionalization would be those with pendant double bonds. If the polymerization of an alkenyl-substituted norbornene proceeds selectively through the endocyclic double bond, the exocyclic pendant double bond is a versatile group for its transformation into other functional groups by addition reactions, [18][19][20] epoxidation, 19,21,22 cyclopropanation, 19 etc. 23,24 Particularly, alkenyl-monomers with a terminal unsaturation, such as the accessible and commercially available 5-vinyl-2norbornene (VNB), are especially interesting.…”
Section: Introductionmentioning
confidence: 99%
“…Instruments and Characterization. 1 H, 13 C, and 19 F nuclear magnetic resonance (NMR) spectra were recorded at room temperature (ca. 25 °C) using a Bruker Ascend 400 MHz NMR spectrometer.…”
Section: ■ Introductionmentioning
confidence: 99%